Phylogenetic footprint of the plant clock system in angiosperms: evolutionary processes of Pseudo-Response Regulators - Saito Shigeru; Takata Naoki; Saito Claire; Uemura Matsuo (BMC Evolutionary Biology, 2010)
Abstract Background Plant circadian clocks regulate many photoperiodic and diurnal responses that are conserved among plant species. The plant circadian clock system has been uncovered in the model plant, Arabidopsis thaliana, using genetics and systems biology approaches. However, it is still not clear how the clock system had been organized in the evolutionary history of plants. We recently revealed the molecular phylogeny of LHY/CCA1 genes, one of the essential components of the clock system. The aims of this study are to reconstruct the phylogenetic relationships of angiosperm clock-associated PRR genes, the partner of the LHY/CCA1 genes, and to clarify the evolutionary history of the plant clock system in angiosperm lineages. Results In the present study, to investigate the molecular phylogeny of PRR genes, we performed two approaches: reconstruction of phylogenetic trees and examination of syntenic relationships. Phylogenetic analyses revealed that PRR genes had diverged into three clades prior to the speciation of monocots and eudicots. Furthermore, copy numbers of PRR genes have been independently increased in monocots and eudicots as a result of ancient chromosomal duplication events. Conclusions Based on the molecular phylogenies of both PRR genes and LHY/CCA1 genes, we inferred the evolutionary process of the plant clock system in angiosperms. This scenario provides evolutionary information that a common ancestor of monocots and eudicots had retained the basic components required for reconstructing a clock system and that the plant circadian clock may have become a more elaborate mechanism after the speciation of monocots and eudicots because of the gene expansion that resulted from polyploidy events.